Acute type A aortic dissection: Aortic Dissection Detection Risk Score in emergency care – surgical delay because of initial misdiagnosis. Issue 3 (1st October 2020) - Zaschke, Lisa; Habazettl, Helmut; Thurau, Jana; Matschilles, Christian; Göhlich, Amélie; Montagner, Matteo; Falk, Volkmar; Kurz, Stephan D
Abstract : Background: Acute type A aortic dissection requires immediate surgical treatment, but the correct diagnosis is often delayed. This study aimed to analyse how initial misdiagnosis affected the time intervals before surgical treatment, symptoms associated with correct or incorrect initial diagnosis and the potential of the Aortic Dissection Detection Risk Score to improve the sensitivity of initial diagnosis. Methods: We conducted a retrospective analysis of 350 patients with acute type A aortic dissection. Patients were divided into two groups: initial misdiagnosis (group 0) and correct initial diagnosis of acute type A aortic dissection (group 1). Symptoms were analysed as predictors for the correct or incorrect initial diagnosis by multivariate analysis. Based on these findings, the Aortic Dissection Detection Risk Score was calculated retrospectively; a result ⩾2 was defined as a positive score. Results: The early suspicion of aortic dissection significantly shortened the median time from pain to surgical correction from 8.6 h in patients with an initial misdiagnosis to 5.5 h in patients with the correct initial diagnosis ( p <0.001). Of all acute type A aortic dissection patients, 49% had a positive Aortic Dissection Detection Risk Score. Of all initial misdiagnosed patients, 41% had a positive score (⩾2). The presence of lumbar pain ( p <0.001), any paresis ( p =0.037) and sweating ( p =0.042) was more likely to lead to the correct initial diagnosis. Conclusion: An early consideration of acute aortic dissection may reduce the delay of surgical care. The suggested Aortic Dissection Detection Risk Score may be a useful tool to improve the preclinical assessment.